Diabetic retinopathy further increases risk of cardiovascular disease mortality in a high-risk cohort - Richard Kha; Yasemin Kapucu; Mayuri Indrakumar; George Burlutsky; Aravinda Thiagalingam; Pramesh Kovoor; Paul Mitchell; Gerald Liew (Scientific Reports, 2025)
Abstract Diabetic retinopathy (DR) is the most common microvascular complication of diabetes and is strongly linked with systemic vascular comorbidities. This study investigated if DR predicts risk of cardiovascular disease (CVD) mortality in a high CVD risk cohort. This was a prospective cohort study of 1582 adult participants who presented to a tertiary Australian hospital for evaluation of acute coronary syndrome by coronary angiography. Participants were concurrently examined for DR from mydriatic fundus photographs which were mask-graded according to International Clinical Classification categories of no DR, mild non-proliferative DR, moderate-to-severe NPDR, and proliferative DR. Coronary artery disease was graded from coronary angiograms using the Gensini score. CVD mortality follow-up was assessed 9 years after baseline examination using linkage with the Australian National Death Index. At baseline, 355 (22.4%) participants had any DR. There were 181 (11.4%) fatal CVD events after 9-years follow-up. After controlling for age, sex, BMI, diabetes, total cholesterol, smoking status, hypertension, previous myocardial infarction and stroke, any DR was associated with 1.8-fold higher risk of CVD mortality (Hazard Ratio [HR] 1.84, 95% Confidence Interval [95% CI: 1.30–2.61]). Mild non-proliferative DR (1.85 [1.26–2.72]) and proliferative DR (5.27 [2.32–12.00]) were associated with greater CVD mortality risk. Further adjustment for coronary artery disease using Gensini scores and excluding patients without diabetes had minimal impact on the association. The increased risk of CVD mortality was significant in both men (2.25 [1.60–3.19]) and women (2.38 [1.24–4.58]) with any DR. In individuals with high CVD risk, presence of DR independently predicts increased CVD mortality. This likely reflects additional contribution of microvascular disease to CVD mortality. Individuals with DR may benefit from a comprehensive cardiovascular risk assessment, lifestyle changes, more intensive cardiovascular management and follow-up to minimise risk of death from CVD events.